EFFECTS OF TRIMETAZIDINE ON THE TRANSMITRAL BLOOD FLOW IN PATIENTS WITH DIASTOLIC HEART FAILURE - Yu. N. Fedulaev; N. S. Pavlyuchenko; T. V. Pinchuk; S. Kh. Galachieva; A. A. Kozina; V. N. Ryzhenkov (Столичная издательская компания, 2015)
Aim. To study effects of trimetazidine on the left ventricular diastolic dysfunction in patients with combination of ischemic heart disease (IHD) and arterial hypertension (HT). Material and methods. Patients with IHD and HT (n=154) were divided into two treatment groups. Patients of the main groups (n=72) received standard therapy and trimetazi- dine 35 mg twice a day. The patients of the control group (n=82) received only standard therapy. Echocardiographic parameters, including mitral Doppler flow indices were as- sessed at baseline and after 2 months.Subgroups of patients were identified by type of left ventricle diastolic function according to echocardiographic data. Changes in echocardiographic indicators were evaluated in these subgroups separately and compared in the main and control groups.Results. The subgroups of patients with impaired relaxation (n=54), pseudonormalization (n=48) and restriction (n=52) were identified in the main and control groups according to echocardiographic data. A significant increase in the period of early left ventricle filling (27.6%, p<0.05) and the ratio of the two phases of left ventricle filling (37.8%, p<0.001) were found in patients with impaired relaxation treated with trimetazidine. Other studied parameters of mitral flow in the other patient subgroups were not significantly changed. Conclusion. Trimetazidine 70 mg daily in the 2 month treatment of diastolic heart failure in patients with IHD and HT resulted in significant improvement of some indicators of mitral blood flow only in patients with type I diastolic dysfunction (impaired relaxation).